Hesitancy towards COVID-19 booster vaccine among healthcare workers in Bangladesh - Homayra Rahman Shoshi; Ahamed Khairul Basher; Ashrak Shad Pyash; Md. Kamal Hossain; Fahmida Chowdhury; Md Zakiul Hassan (BMC Health Services Research)
Abstract Background Despite completing the COVID-19 vaccination series, healthcare workers (HCWs) remain at an elevated risk of re-infection. Booster uptake, though essential for this group, remains poorly characterized among Bangladeshi HCWs. This study identified the prevalence and driving factors behind booster hesitancy among Bangladeshi HCWs, providing valuable insights for targeted interventions. Method From December 2022 to June 2023, we conducted a cross-sectional survey among 1772 HCWs enrolled from 20 healthcare facilities of all tiers purposively selected across four administrative divisions of Bangladesh. We collected information through face-to-face interviews regarding their sociodemographic, pre-existing, and currently existing medical conditions, COVID-19 vaccination status, and their intention, hesitancy, and willingness to receive future booster doses. We used a multivariable logistic regression model to analyze factors associated with booster hesitancy. Odd’s ratio with 95% confidence intervals (CIs) was calculated for each factor, with p < 0.05 considered statistically significant. Result Of the 1772 HCWs interviewed in our study, 49% (879) were nurses [median age 36 years (IQR: 30.0-46.0)]; 69% were female. Among the respondents, 94% (1667) were willing to take a booster, and 6% (105) showed hesitancy. Safety concerns, especially regarding potential side effects post-booster administration (86%), emerged as the leading cause of booster hesitancy among healthcare workers. Our multivariable logistic regression analysis revealed that support staff, compared to physicians, were the most hesitant to receive any additional booster dose (aOR 4.68, 95% CI: 1.56-9.03; p=0.006). Compared to rural residency, HCWs with an urban residency type were also more reluctant to receive booster doses (aOR 4.45, 95% CI: 2.03-9.73; p < 0.001). Conclusion Concerns about side effects following booster administration were the primary driver of hesitancy in our study. Targeted interventions focusing on education and addressing these anxieties—supported by evidence-based communication strategies—could play a crucial role in improving booster acceptance and safeguarding this vulnerable workforce.